2013
DOI: 10.1371/journal.pone.0057238
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR to Detect and Quantify Heteroresistance in Drug Resistant Mycobacterium tuberculosis

Abstract: Drug resistance in Mycobacterium tuberculosis presents an enormous public health threat. It is typically defined as >1% of drug resistant colonies using the agar proportion method. Detecting small numbers of drug resistant Tb in a population, also known as heteroresistance, is challenging with current methodologies. Here we have utilized digital PCR to detect heteroresistance within M. tuberculosis populations with excellent accuracy versus the agar proportion method. We designed dual TaqMan-MGB probes to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 13 publications
2
57
0
Order By: Relevance
“…Consequently, the Sanger sequencing and qPCR tests may not be able to detect antibiotic-resistant subpopulations of L. pneumophila in the early stage of infection in legionellosis patients. The dPCRgyrA sensitivity levels observed in this study are similar to those previously reported by Pholwat et (23). In the literature, the maximum sensitivity reported for dPCR is 0.001% (one mutant sequence for 100,000 wild-type sequences) (28)(29)(30).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, the Sanger sequencing and qPCR tests may not be able to detect antibiotic-resistant subpopulations of L. pneumophila in the early stage of infection in legionellosis patients. The dPCRgyrA sensitivity levels observed in this study are similar to those previously reported by Pholwat et (23). In the literature, the maximum sensitivity reported for dPCR is 0.001% (one mutant sequence for 100,000 wild-type sequences) (28)(29)(30).…”
Section: Discussionsupporting
confidence: 91%
“…dPCR has wide clinical applications in the oncology field (14) and ongoing applications in noninvasive prenatal diagnosis (15,16) and organ transplant rejection monitoring (17). For infectious diseases, dPCR technology has been mainly used for the diagnosis of viral diseases (13), the quantification of bacteria in clinical samples (18)(19)(20)(21), the detection and quantification of antibiotic resistance genes (22,23), and the detection and quantification of bacterial toxins (24).…”
mentioning
confidence: 99%
“…For example, one isolate harbored an rpoB resistance-mediating mutation (CCG [Pro] at codon 452) in 19% of the total population, as deduced from our WGS data, which is below the limit of detection by Sanger sequencing (Fig. 4) (33). One discordant SNP is covered by the reverse primer used for Sanger sequencing, which leads to a wild-type call (data not shown).…”
Section: Resultsmentioning
confidence: 78%
“…Thus, NGS could potentially offer a better understanding of the population structure in clinical samples. Digital PCR may be another alternative to detect heteroresistance more precisely (18).…”
mentioning
confidence: 99%